2018
DOI: 10.1253/circj.cj-18-0744
|View full text |Cite
|
Sign up to set email alerts
|

Trifecta vs. Magna for Aortic Valve Replacement ― Differences in Clinical Outcome and Valve Hemodynamics ―

Abstract: Postoperative outcomes were similar for both valves. An early hemodynamic advantage for the Trifecta valve lasted to approximately 1 year postoperatively but did not persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
(11 reference statements)
3
19
0
Order By: Relevance
“…Tadokoro et al showed that the early hemodynamic advantage of the Trifecta valve lasted for up to 1 year postoperatively. Thereafter, this difference diminished gradually over time [14]. These results are partially consistent with our findings, showing that the differences in the TVPG between the two groups did not change over time, with the only exception being the time immediately after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Tadokoro et al showed that the early hemodynamic advantage of the Trifecta valve lasted for up to 1 year postoperatively. Thereafter, this difference diminished gradually over time [14]. These results are partially consistent with our findings, showing that the differences in the TVPG between the two groups did not change over time, with the only exception being the time immediately after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the authors have shown much higher late postoperative gradients in the smaller valve sizes with the 19-mm Trifecta having increased mean gradients to 18 mm Hg starting at 6 months postoperatively. This is similar to reported results in competing stented tissue valves [3]. Although the Trifecta's unique design can improve hemodynamics (early anyway), it creates a new problem with our TAVR mindset.…”
Section: Invited Commentarysupporting
confidence: 85%
“…In addition, we did not randomise the prosthetic valve selection (Avalus™ or other valves) in this study; instead, the valves were selected by individual surgeons who implanted the best-matched valve prosthesis for each patient. Because the Avalus™ valve was the primary choice of bioprosthetic valve during the study period, the study bias related to patient selection was minimal [14,15].…”
Section: Discussionmentioning
confidence: 99%